"Fui estrangeiro, e vocês me acolheram": acolhimento aos migrantes venezuelanos em Boa Vista - RR por meio das igrejas evangélicas - Mota, Warlison Monteiro (2022)
The development of the present research made possible an analysis of the social importance of evangelical churches in the work with Venezuelan immigrants in Roraima, a reflection on the social role of these churches as institutions that offer reception, in addition, it also allowed to observe that immigration brought changes to the churches and for Roraima society, as they had to use different resources to perform reception. The gospel awakens the human being for social promotion and the converted subject manifests this state of mind to be useful to his neighbor. Brazil has received many immigrants and refugees, and the important role of churches in welcoming and supporting these vulnerable people stands out. In analyzing the process of welcoming Venezuelan immigrants, it is necessary to identify the theological directions of the evangelical churches. To analyze the work carried out in Roraima, we will use theological models of immigration. The research aims to analyze the theological directions of the churches in the actions of reception, from the scenario developed for the humanitarian intervention in the state of Roraima. The present work is a research with a basic strategic purpose, with descriptive and exploratory objectives, carried out by the deductive method, with a qualitative approach and carried out through a bibliographic and documentary survey.